Effect of Combined Light Quality and Calcium Chloride Treatments on Growth and Quality of Chinese Kale Sprouts - Hongxia Li; Wenjuan Cheng; Xuena Yu; Kehao Liang; Yi Tang; Zhi Huang; Huanxiu Li; Fen Zhang; Cunkun Chen; Bo Sun (Horticulturae)
Chinese kale sprouts are widely cultivated and consumed due to their elevated nutritional worth and ease of cultivation in controlled environments. This study focused on the effects of several light types (white, red, and blue) both by themselves and in conjunction with calcium chloride (CaCl2) on the physiological development and nutritional value of Chinese kale sprouts. Analysis proved that under differing light treatments, white light resulted in the highest pigment content, and red light markedly increased plant height, fresh mass, and soluble sugar accumulation. Additionally, blue light significantly enhanced the antioxidant capacity. When light quality and calcium chloride were applied together, fresh mass increased by 9.50%, 9.85%, and 12.47% (compared with single light treatments), and significantly elevated the indolic glucosinolate content. Besides, red light combined with calcium chloride also enhanced the antioxidant capacity (ferric reducing antioxidant power (FRAP) content) compared with red light alone, increasing by 14.31%. This research determined that red light in conjunction with calcium chloride obtained the highest yield of sprouts, and it can also offer new strategies for increasing the antioxidant capacity, while the blue light in conjunction with calcium chloride can provide more ways for accumulating glucosinolates. In conclusion, incorporating light quality and calcium chloride treatments in Chinese kale sprout cultivation is an effective approach for increasing yield and quality.